2015
DOI: 10.1083/jcb.201506002
|View full text |Cite
|
Sign up to set email alerts
|

ARF6–JIP3/4 regulate endosomal tubules for MT1-MMP exocytosis in cancer invasion

Abstract: Interaction of plasma membrane ARF6 with JIP3/JIP4 effectors on MT1-MMP endosomes coordinates dynactin–dynein and kinesin-1 activity in a tug-of-war mechanism for endosome tubulation and MT1-MMP exocytosis to promote breast cancer cell invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
115
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(137 citation statements)
references
References 55 publications
21
115
1
Order By: Relevance
“…Our current study (Figures 6E–G) supports the previous finding that ARF6 is not required for the recruitment of KIF5B to MT1-MMP vesicles (Castro-Castro et al, 2016; Marchesin et al, 2015). Therefore, the recruitment of KIF5B to MT1-MMP on late endosomes/lysosomes for its recycling is a PLD2-dependent but ARF6-independent process, which is different from the biogenesis of syntenin exosomes and HIV-1 budding.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our current study (Figures 6E–G) supports the previous finding that ARF6 is not required for the recruitment of KIF5B to MT1-MMP vesicles (Castro-Castro et al, 2016; Marchesin et al, 2015). Therefore, the recruitment of KIF5B to MT1-MMP on late endosomes/lysosomes for its recycling is a PLD2-dependent but ARF6-independent process, which is different from the biogenesis of syntenin exosomes and HIV-1 budding.…”
Section: Discussionsupporting
confidence: 92%
“…The requirement of PLD2-generated PA for recruitment of KIF5B to MT1-MMP vesicles is different from ARF6, a known PLD2 activator (Ghossoub et al, 2014; Honda et al, 1999). ARF6 promotes the fusion of MT1-MMP vesicles with the plasma membrane, and is not involved in the recruitment of KIF5B to MT1-MMP vesicles (Castro-Castro et al, 2016; Marchesin et al, 2015). We also found that knockdown of ARF6 had no effect on the localization of KIF5B to MT1-MMP vesicles (Figures 6E–G), supporting the previous finding (Marchesin et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MT1-MMP is dynamically internalized by both clathrin- and caveolar-mediated endocytosis and directed via a Rab5 early endosome vesicle trafficking pathway to either a Rab4 fast recycling exocytosis pathway (thought to be a minor component of MT1-MMP recycling) or through Rab7 delivery to late endosome/endolysosome where most MT1-MMP accumulates. Following accumulation in the late endosome/endolysosome, MT1-MMP is trafficked and exocytosed back to invadopodia through an Arf6, endosomal WASH protein, exocyst complex, and V-SNARE protein VAMP-7 mediated mechanism (Frittoli et al, 2014; Linder, 2015; Marchesin et al, 2015; Monteiro et al, 2013; Poincloux et al, 2009; Remacle et al, 2003; Williams and Coppolino, 2011). MT1-MMP is stabilized at invadopodia in the plasma membrane by a direct interaction with invadopodial F-actin, providing a link between the F-actin core of invadopodia and the invadopodial membrane (Yu et al, 2012).…”
Section: The Specialized Invadopodial Membrane May Be Conserved In Otmentioning
confidence: 99%
“…Furthermore, endocytic trafficking is used to add membrane during cytokinesis (Grant and Donaldson, 2009). Adding weight to the notion that the endolysosome delivers membrane to invadopodia, the GTPase Arf6 together with its effectors JIP3 and JIP4 mediate the delivery of endosomes for membrane addition during cytokinesis and regulate exocytosis of MT1-MMP (Marchesin et al, 2015; Montagnac et al, 2009). Thus, the molecular machinery of the vesicular trafficking system is present for rapid membrane addition to invadopodia to allow for its protrusive activity.…”
Section: Function Of the Invadopodial Membranementioning
confidence: 99%